Not the apocalypse I was hoping for - Greentree, Leslie (Brave & brilliant series, 2022)
"Award-winning author Leslie Greentree presents fourteen short stories in this dark, often funny, deeply compelling collection that asks how we locate, create, and avoid meaning In our lives. These are stories about people and relationships challenged by death and redeemed by art. Satirical, political, personal, and tender, they take us to funerals, protests, art galleries, to the dark side of the service industry, and through cities on fire. An actress turns her terminal cancer diagnosis into an art instillation; a boy's attempt at a practical joke derails his grandfather's funeral; a mother discovers she may care more for her sick dog than her newborn son; a man watches his dream of becoming a #hero burn with the city around him; a teacher befriends a gargoyle; a coalition of women fighting for bodily autonomy turn to the ultimate shock-performance protest. Taking on the social collective, the performance of death, the political battleground, and the search for existential happiness with fearlessness and verve, Not the Apocalypse I Was Hoping For is full of sharp observation, irreverence, wit, and compassion."--